Investigation of rare earth-doped ceramics as thermal barrier coating materials - Wang, Jing (2016)
Increasing operating temperatures of gas engines is an effective approach to further improve thermal efficiency. But the ceramic top-coat (conventional 7-8 wt% yttria-stabilised zirconia, 7-8YSZ) in thermal barrier coatings (TBCs) cannot afford application temperatures above 1250 oC, the main reason of which is the accelerated phase transformation, due to quick cation diffusion. In addition, 7-8YSZ has relatively large thermal conductivity, small coefficient of thermal expansion (CTE) and large oxygen ion diffusivity. The relatively small CTE could create the mismatch between ceramic top-coat and metallic bond coat in thermal barrier coatings (TBCs), which can generate strain or stress at the interface to cause the spallation of TBCs. The oxygen atoms for the formation of thermally grown oxides (TGO) in TBCs come from ceramic top-coat, but the thickness of TGO cannot exceed 10 μm in order to avoid the spallation of TBCs. Therefore, it is extremely important to find new ceramic candidates to replace 7-8YSZ and to be used at elevated temperatures. According to these critical criteria of ceramic top-coat, three ceramic candidates were chosen and studied, which are stannate with pyrochlore crystal structure, erbia-based oxides stabilised zirconia and yttrium aluminium garnet. All candidates were synthesised using a sol-gel method. Crystalline phases of all as-synthesised powders were characterised by X-ray diffraction (XRD). Thermal conductivity, coefficient of thermal expansion (CTE), phase stability, chemical compatibility were also studied. Furthermore, molecular dynamics (MD) simulations were used to calculate thermal conductivity and CTE, and to analyse and explain experimental results. Pyrochlore has excellent phase stability and relatively low thermal conductivity, but relatively small CTE. From the consideration of crystal structure and ion radius, La3+ doped Yb2Sn2O7 ceramics with pyrochlore crystal structures are investigated as one TBCs candidate material. As La3+ and Yb3+ ions have the largest radius difference in lanthanide group, La3+ ions are expected to produce significant disorders by replacing Yb3+ ions in cation layers of Yb2Sn2O7. Both experimental and computational XRD data and phase analysis are carried out and good agreement has been obtained. The lattice constants of solid solution (LaxYb1-x)2Sn2O7 (x=0.3, 0.5, 0.7) increase linearly when the content of La3+ is increased. The thermal properties (thermal conductivity and coefficients of thermal expansion) have been compared with the traditional 8 wt% yttria-stabilised zirconia (8YSZ) and La2Zr2O7 (LZ). La3+ doped Yb2Sn2O7 exhibits lower thermal conductivities than un-doped stannates and thermal conductivity deceases with the increase of doping concentration, but it reaches a minimum value when x=0.5 then increases again. Thus among (LaxYb1-x) 2Sn2O7 compositions, (La0.5Yb0.5)2Sn2O7 exhibits the lowest thermal conductivity (0.851 W•m-1•K-1 at room temperature), which is much lower than that of 8YSZ (1.353 W•m-1•K-1). Moreover, it possesses a high coefficient of thermal expansion (13.530×10-6 K-1 at 950 oC). In addition, the simulation results obtained from the MD simulations, indicate that the variation of thermal conductivity with increasing doping concentration in solid solution (LaxYb1-x) 2Sn2O7 (x=0.3, 0.5, 0.7) is independent of external effects, like porosity, grain size and grain boundary. Stabilised zirconia is still one of the most popular TBCs top-coat systems, but new stabilisers are still under-seeking. For stabilised zirconia, to improve thermal phase stability and further reduce thermal conductivity are the most urgent challenges. Erbia-based rare earth oxides stabilised zirconia is studied at 1400 oC. XRD patterns confirmed that erbia-stabilised zirconia have the non-transformable phase. Thermal conductivity decreases and thermal phase stability is improved with the increase of the erbia content. Mono- or bi-rare earth oxides doped erbia-stabilised zirconia is studied to further reduce thermal conductivity due to creating cluster defects. The influences on thermal phase stability produced by different dopants are also analysed. The chemical formulas of Mono- or bi-rare earth oxides doped erbia stabilised zirconia are Er0.05R0.05Zr0.9O1.95 (R=Yb, Gd and Dy) and Er0.04R0.04 R*0.04Zr0.88O1.94 (R+R*=Yb+Dy, Yb+Gd and Dy+Gd), respectively. Thermal conductivities of Er0.05R0.05Zr0.9O1.95 (R=Yb, Gd and Dy) and Er0.04R0.04 R*0.04Zr0.88O1.94 (R+R*=Yb+Dy, Yb+Gd and Dy+Gd) are lower than that of conventional 8YSZ and also they exhibit comparable CTEs to 8YSZ. Importantly, it is found that the thermal phase stability is dependent on the tetragonality, c/a√2 ratio. When the c/a√2 ratio decreases from 1.010 to 1.006 for mono- or bi-rare earth oxides doped erbia, the thermal phase stability is better. Yttrium aluminium garnet (YAG) is also an attractive candidate as thermal barrier material, due to its relatively low thermal conductivity, low oxygen diffusivity and good phase stability at elevated temperatures. YAG has a complex crystal structure, in which Y3+ ions locate in dodecahedra and Al3+ ions in octahedra and tetrahedra. Replacing the host cations with rare earth elements can cause the distortion of polyhedrons which influences the thermal properties of YAG. Because the space inside the octahedra are relatively small, Yb3+ ions which have the smallest ionic radial sizes in the lanthanide series, have been selected and doped on dodecahedral and octahedral sites to investigate the effects on thermal conductivity and thermal expansion. The variation of lattice constant indicates that Yb3+ ions are located on the dodecahedra or octahedra. In addition, when Yb3+ ions replace Al3+ ions on octahedral sites, thermal conductivity at room temperature is dramatically reduced and the coefficient of thermal expansion is over 10×10-6 K-1 at high temperatures, which results from the expansion of octahedra due to Yb3+ ions with much larger radii compared with the host cations (Al3+ ions). On the contrary, replacing Y3+ ions with Yb3+ ions in dodecahedra, thermal conductivity gradually reduces but the coefficient of thermal expansion is smaller, due to the relatively small ionic radii of Yb3+ ions causing the contraction of the dodecahedra. Additionally, it is found that the largest decrease in thermal conductivity results from phonon scattering caused by the large atomic mass difference rather than the relatively small difference in ionic radius.